2003
DOI: 10.1080/1462220021000060464
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and smoking cessation among inner-city African Americans using the nicotine patch

Abstract: This study examined the relationship between depressive symptoms and smoking cessation among a sample of inner-city African American smokers using the nicotine patch. Analyses were conducted on data from a previous randomized trial that tested the effects of culturally sensitive vs. standard self-help quitting materials. The study sample consisted of 498 African American smokers (mean age = 42.95, SD = 10.40; 60% female) recruited from a large hospital. Participants in both groups received 8 weeks of nicotine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
0
18
1
Order By: Relevance
“…Depressive symptoms are associated with greater likelihood of smoking and poorer cessation outcomes at the population level (Anda et al, 1990). In clinical trials, higher levels of pretreatment depressive symptoms are associated with reduced odds of cessation (Anda et al, 1990;Brown et al, 2001;Cinciripini et al, 2003;Ginsberg, Hall, Reus, & Muñoz, 1995;Haas, Muñoz, Humfleet, Reus, & Hall, 2004;Hitsman et al, 1999;Killen, Fortmann, Davis, Strausberg, & Varady, 1999;Kinnunen, Doherty, Militello, & Garvey, 1996;Niaura et al, 2001;Rausch, Nichinson, Lamke, & Matloff, 1990;Swan et al, 2003), although this effect has not been replicated in some investigations (Catley, Ahluwalia, Resnicow, & Nazir, 2003;Catley et al, 2005;Vàzquez & Becoña, 1999). Many studies have shown that depressive symptoms, even at very low levels (e.g., Hamilton Rating Scale for Depression score >2; Niaura et al, 2001), predict poorer outcomes in smokers without current major depression (al 'Absi, Hatsukami, & Davis, 2005;al'Absi, Hatsukami, Davis, & Wittmers, 2004;Brown et al, 2001;Cinciripini et al, 2003;Ginsberg et al, 1995;Haas et al, 2004;Killen et al, 1999;Swan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Depressive symptoms are associated with greater likelihood of smoking and poorer cessation outcomes at the population level (Anda et al, 1990). In clinical trials, higher levels of pretreatment depressive symptoms are associated with reduced odds of cessation (Anda et al, 1990;Brown et al, 2001;Cinciripini et al, 2003;Ginsberg, Hall, Reus, & Muñoz, 1995;Haas, Muñoz, Humfleet, Reus, & Hall, 2004;Hitsman et al, 1999;Killen, Fortmann, Davis, Strausberg, & Varady, 1999;Kinnunen, Doherty, Militello, & Garvey, 1996;Niaura et al, 2001;Rausch, Nichinson, Lamke, & Matloff, 1990;Swan et al, 2003), although this effect has not been replicated in some investigations (Catley, Ahluwalia, Resnicow, & Nazir, 2003;Catley et al, 2005;Vàzquez & Becoña, 1999). Many studies have shown that depressive symptoms, even at very low levels (e.g., Hamilton Rating Scale for Depression score >2; Niaura et al, 2001), predict poorer outcomes in smokers without current major depression (al 'Absi, Hatsukami, & Davis, 2005;al'Absi, Hatsukami, Davis, & Wittmers, 2004;Brown et al, 2001;Cinciripini et al, 2003;Ginsberg et al, 1995;Haas et al, 2004;Killen et al, 1999;Swan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is unclear what factors influence the likelihood that a young adult smoker would participate in a formal smoking cessation program. Prior research in older adults suggests a host of factors (e.g., demographic, smoking history, social, and psychological) may contribute to nonparticipation in smoking cessation programs (8)(9)(10)(11)(12). These factors include gender, race, education, smoking rate, and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study was to evaluate the predictors of participation in a smoking cessation program among young adult smokers. We evaluated variables shown to be important in older adult smoking cessation programs and those variables associated with young adult smoking (8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms underlying African American-White differences in quitting are also not well understood. Multiple factors, including demographic (e.g., socioeconomic status) [29, 33, 36, 37] and smoking characteristics (e.g., menthol, nicotine intake) [3942], adherence and/or response to treatment (e.g., reductions in withdrawal, craving) [18, 17, 27, 31, 43], psychosocial (e.g., psychological distress, perceived and contextual disadvantage, stress) [4446, 24, 4753], and biological factors linked to nicotine metabolic inactivation (e.g., CYP2A6, 3hydroxycotinine/cotinine) [5458] have been studied as they relate to cessation in African Americans and Whites, separately, but few studies have explored the relative importance of these factors in explaining African American-White differences in quitting.…”
mentioning
confidence: 99%